Midwives' Attitudes Toward and Experience With a Tablet Intervention to Promote Safety Behaviors for Pregnant Women Reporting Intimate Partner Violence: Qualitative Study - Garnweidner-Holme, Lisa; Henriksen, Lena; Flaathen, Eva Marie; Klette Bøhler, Tone; Lukasse, Mirjam (JMIR Publications, 2020)
BackgroundViolence against women is considered a global health problem, and intimate partner violence (IPV) around the time of childbirth can have severe consequences for mother and child. Prenatal care is considered a window of opportunity to address IPV and ask women about exposure to violence since women are in regular contact with health care providers. Mobile health (mHealth) interventions might overcome the barriers to talking about IPV face-to-face. ObjectiveOur objective was to explore midwives' attitudes toward a tablet intervention consisting of information about IPV and safety behaviors as well as their experiences with recruiting pregnant women of different ethnic backgrounds in a randomized controlled trial (RCT). MethodsIndividual interviews were conducted with 9 midwives who recruited participants for an RCT to test a video to promote safety behaviors delivered on a tablet during prenatal care. Analysis was guided by thematic analysis. ResultsMidwives perceived the tablet intervention as an appropriate supplement during prenatal care to provide information about IPV and promote safety behaviors. They participated in the RCT primarily to obtain more knowledge regarding how to communicate about IPV. The intervention was perceived as an anonymous door-opener to talk about IPV and a good solution to ensure that every woman gets the same information. However, the content of the intervention had to be trustworthy and align with the information the midwives provide to women. Given the sensitivity of IPV, midwives outlined the importance of following the intervention with face-to-face communication. Midwives reported technical problems and a high demand on their time as the main challenges to recruiting women. They experienced challenges recruiting women of different ethnic backgrounds due to linguistic barriers and the women's skepticism about scientific research. ConclusionsThe tablet intervention might help midwives communicate about IPV. Although the video was considered as an anonymous door-opener to talk about IPV, midwives outlined the importance of following the intervention with face-to-face communication. The scarcity of midwives' time during consultations has to be considered when implementing the intervention. Further research is needed to overcome barriers that limit inclusion of women from different ethnic backgrounds. Trial RegistrationClinicalTrials.gov NCT03397277; https://clinicaltrials.gov/ct2/show/NCT03397277